Neuroinflammation in glaucoma: a myriad of cellular pathways and players - Michael MacLean; Sean D. Lydon; Cátia Gomes; Elizabeth M. Pizzi; Cory A. Diemler; Sarah E. R. Yablonski; Gareth R. Howell; Jason S. Meyer; Richard T. Libby (Mammalian Genome, 2026)
Glaucoma is a complex neurodegenerative disease with multiple subtypes, yet all are characterized by the progressive dysfunction and loss of retinal ganglion cells (RGCs), which ultimately results in vision impairment and blindness. Elevated intraocular pressure (IOP) is a major risk factor for glaucoma; however, it is neither necessary nor sufficient for glaucomatous neurodegeneration, as patients can exhibit high IOP without developing glaucoma and patients can develop glaucoma with normal IOP. Yet FDA-approved treatment options are largely limited to approaches to minimize risk and reduce IOP. Thus, there is a critical need to target other aspects of glaucoma pathophysiology. Neuroinflammation is broadly defined here as immune-relevant responses, often involving microglia and astrocytes, within the central nervous system which may include peripheral immune cell infiltration. Burgeoning evidence has implicated glia in the development and progression of glaucoma in human tissues and mouse models. Most mouse models of glaucoma to date have shown that microglia and astrocytes are reactive in early stages of glaucomatous neurodegeneration prior to overt RGC loss. However, there is growing evidence that human and mouse glia adopt distinct phenotypes in response to neurodegeneration. Thus, there is critical need to expand our studies to include the new generations of human cell culture models. In this review, we discuss: 1) the evidence of neuroinflammatory processes in human glaucoma; 2) models of glaucoma relevant neuroinflammation; and the evidence specifically for 3) innate immune cell-driven and 4) macroglia-driven processes.

Vascular contribution to cognitive impairment and dementia (VCID): proceedings of 2025 workshop of the Jackson Laboratory - Mehwish Anwer; Tetiana Poliakova; Ricardo D’Oliveira Albanus; Mohammad Iqbal H. Bhuiyan; Adam M. Brickman; Soumilee Chaudhuri; Leah Cuddy; Maxwell Eisenbaum; Kate Foley; Douglas B. Gould; Catherine Hall; Costantino Iadecola; et al. (Mammalian Genome, 2026)
The first Vascular Contributions to Cognitive Impairment and Dementia (VCID) Workshop, held on May12-16, 2025 at The Jackson Laboratory, provided scientific content and career development training in the latest developments in VCID and Alzheimer’s Disease (AD) and related dementia (ADRD). The Workshop aimed to foster interdisciplinary collaborations and empower the next generation of diverse scientists to advance ADRD research from mechanism to intervention. The meeting placed a strong emphasis on neurovascular pathology, its central role in ADRD pathogenesis, its modulation by both central and peripheral factors, and the critical need to dissect the mechanistic basis of VCID through experimental models. The workshop included talks from both faculty and trainees and was bookended by two keynote addresses by Drs. Donna Wilcock and Costantino Iadecola, leaders and pioneers in the VCID field. The second VCID workshop is planned for April 28-May 1, 2026, to be held at Washington University in St. Louis.

Characterization of adult hippocampal neurogenesis in adult and aged genetically diverse mice - Adele E. Finch; Avery D. McNamara; Kristen D. Onos; Kelly J. Keezer; Gareth R. Howell; Ashley E. Webb (GeroScience, 2025)
Adult hippocampal neurogenesis—the generation of new neurons in the adult brain—declines with age, contributing to cognitive deficits in aging. While the majority of mammalian studies on neurogenesis have utilized inbred mouse strains, these models do not fully capture the genetic diversity of humans, limiting the translational relevance of their findings. The Diversity Outbred (DO) mouse model, a genetically heterogeneous population, provides a promising alternative to traditional inbred strains. In this study, we investigated how genetic diversity influences hippocampal neurogenesis by comparing neurogenesis in adult and aged Diversity Outbred (DO) mice with the commonly used C57BL/6J inbred strain. While both strains exhibited a decline in neurogenesis with age, DO mice showed significantly lower levels of neurogenesis compared to C57BL/6J mice, even in young adults. Additionally, we observed that the wild-derived CAST/EiJ strain, one of the eight founder strains in the DO model, contributed to this reduction in neurogenesis. Our findings highlight the importance of genetic diversity in neurogenesis research and suggest that the DO model may better represent human genetic diversity associated with age-related decline in neurogenesis.

Co‐Existence Slows Diversification in Experimental Populations of E. coli and P. fluorescens - Gareth Howells; Aysha L. Sezmis; Christopher Blake; Michael J. McDonald (Environmental Microbiology, 2025)
Microbes grown in heterogeneous laboratory environments can rapidly diversify into multiple, coexisting variants. While the genetic and evolutionary mechanisms of laboratory adaptive radiations are well studied, how the presence of other species alters the outcomes of diversification is less well understood. To test the effect of co‐culture growth on the Pseudomonas fluorescens SBW25 adaptive radiation, Escherichia coli and P. fluorescens were cultured in monoculture and co‐culture for 8 weeks. In P. fluorescens monoculture, Wrinkly and Smooth Spreader types rapidly evolved and were maintained over 8 weeks, while E. coli monocultures evolved two colony types, a big and a small colony variant. In contrast, we found that in co‐culture, E. coli did not evolve small colony variants. Whole genome sequencing revealed the genetic basis of possible co‐culture specific adaptations in both E. coli and P. fluorescens . Altogether, our data support that the presence of multiple species changed the outcome of adaptive radiation.

Extended gene panel testing in lobular breast cancer - Elke M. van Veen; D. Gareth Evans; Elaine F. Harkness; Helen J. Byers; Jamie M. Ellingford; Emma R. Woodward; Naomi L. Bowers; Andrew J. Wallace; Sacha J. Howell; Anthony Howell; Fiona Lalloo; William G. Newman; et al. (Familial Cancer, 2022)
Purpose : Lobular breast cancer (LBC) accounts for ~ 15% of breast cancer. Here, we studied the frequency of pathogenic germline variants (PGVs) in an extended panel of genes in women affected with LBC. Methods : 302 women with LBC and 1567 without breast cancer were tested for BRCA1/2 PGVs. A subset of 134 LBC affected women who tested negative for BRCA1/2 PGVs underwent extended screening, including: ATM, CDH1, CHEK2, NBN, PALB2, PTEN, RAD50, RAD51D, and TP53. Results : 35 PGVs were identified in the group with LBC, of which 22 were in BRCA1/2 . Ten actionable PGVs were identified in additional genes ( ATM (4), CDH1 (1), CHEK2 (1), PALB2 (2) and TP53 (2)). Overall, PGVs in three genes conferred a significant increased risk for LBC. Odds ratios (ORs) were: BRCA1 : OR = 13.17 (95%CI 2.83–66.38; P = 0.0017), BRCA2 : OR = 10.33 (95%CI 4.58–23.95; P < 0.0001); and ATM: OR = 8.01 (95%CI 2.52–29.92; P = 0.0053). We did not detect an increased risk of LBC for PALB2, CDH1 or CHEK2 . Conclusion : The overall PGV detection rate was 11.59%, with similar rates of BRCA1/2 (7.28%) PGVs as for other actionable PGVs (7.46%), indicating a benefit for extended panel genetic testing in LBC. We also report a previously unrecognised association of pathogenic variants in ATM with LBC.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Localized outbreaks of coral disease on Arabian reefs are linked to extreme temperatures and environmental stressors - Greta Smith Aeby; Emily Howells; Thierry Work; David Abrego; Gareth J. Williams; Lisa M. Wedding; Jamie M. Caldwell; Monica Moritsch; John A. Burt (Coral Reefs, 2020)
The Arabian Peninsula borders the hottest reefs in the world, and corals living in these extreme environments can provide insight into the effects of warming on coral health and disease. Here, we examined coral reef health at 17 sites across three regions along the northeastern Arabian Peninsula (Persian Gulf, Strait of Hormuz and Oman Sea) representing a gradient of environmental conditions. The Persian Gulf has extreme seasonal fluctuations in temperature and chronic hypersalinity, whereas the other two regions experience more moderate conditions. Field surveys identified 13 coral diseases including tissue loss diseases of unknown etiology (white syndromes) in Porites, Platygyra , Dipsastraea , Cyphastrea, Acropora and Goniopora ; growth anomalies in Porites, Platygyra and Dipsastraea ; black band disease in Platygyra , Dipsastraea , Acropora, Echinopora and Pavona ; bleached patches in Porites and Goniopora and a disease unique to this region, yellow-banded tissue loss in Porites . The most widespread diseases were Platygyra growth anomalies (52.9% of all surveys), Acropora white syndrome (47.1%) and Porites bleached patches (35.3%). We found a number of diseases not yet reported in this region and found differential disease susceptibility among coral taxa. Disease prevalence was higher on reefs within the Persian Gulf (avg. 2.05%) as compared to reefs within the Strait of Hormuz (0.46%) or Oman Sea (0.25%). A high number of localized disease outbreaks (8 of 17 sites) were found, especially within the Persian Gulf (5 of 8 sites). Across all regions, the majority of variation in disease prevalence (82.2%) was associated with the extreme temperature range experienced by these corals combined with measures of organic pollution and proximity to shore. Thermal stress is known to drive a number of coral diseases, and thus, this region provides a platform to study disease at the edge of corals’ thermal range.

Should unaffected female BRCA2 pathogenic variant carriers be told there is little or no advantage from risk reducing mastectomy? - D. Gareth Evans; Sacha J. Howell; Anthony Howell (Familial Cancer, 2019)

Episodic diamond growth beneath the Kaapvaal Craton at Jwaneng Mine, Botswana - Michael U. Gress; Daniel Howell; Ingrid L. Chinn; Laura Speich; Simon C. Kohn; Quint van den Heuvel; Ellen Schulten; Anna S. M. Pals; Gareth R. Davies (Mineralogy and Petrology, 2018)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Breast cancer risk assessment in 8,824 women attending a family history evaluation and screening programme - D. Gareth R. Evans; Sarah Ingham; Sarah Dawe; L. Roberts; F. Lalloo; A. R. Brentnall; P. Stavrinos; Anthony Howell (Familial Cancer, 2014)

High throughput sequencing approaches to mutation discovery in the mouse - Michelle M. Simon; Ann-Marie Mallon; Gareth R. Howell; Laura G. Reinholdt (Mammalian Genome, 2012)

Adult weight gain and central obesity in women with and without a family history of breast cancer: a case control study - Michelle N. Harvie; Saba Bokhari; Andrew Shenton; Linda Ashcroft; Gareth Evans; Ric Swindell; Anthony Howell (Familial Cancer, 2007)

Transgenic rescue of the mouse t complex haplolethal locus Thl1 - Gareth R. Howell; Robert J. Munroe; John C. Schimenti (Mammalian Genome, 2005)

A candidate gene for congenital bilateral isolated ptosis identified by molecular analysis of a de novo balanced translocation - Tristan F. McMullan; John A. Crolla; Simon G. Gregory; Nigel P. Carter; Rachel A. Cooper; Gareth R. Howell; David O. Robinson (Human Genetics, 2002)

Physical and transcriptional mapping of the X-linked cleft palate and ankyloglossia (CPX) critical region - Claire Braybrook; Georgina Warry; Gareth Howell; Vanessa Mandryko; Alfred Arnason; Arni Bjornsson; Mark T. Ross; Gudrun E. Moore; Philip Stanier (Human Genetics, 2001)